Study on the Development Trend of Cross-Border E-Commerce from the Perspective of Global Value Chains - Han, Siyu (International Journal of Global Economics and Management, 2024)
As China's cross-border e-commerce increasingly deepens its participation in the global value chain division of labor, the rapid development of cross-border e-commerce has driven the import behavior of intermediate goods and provided endogenous motivation for the growth of cross-border e-commerce. From the perspective of the global value chain, the development of cross-border e-commerce presents a new trend. Cross-border e-commerce platforms with a single transaction function can no longer meet the needs of era development under the global value chain. This paper explores the development trends of cross-border e-commerce and its impact on the global economy from the perspective of the Global Value Chain (GVC), and proposes several reflections to achieve further development of China's cross-border e-commerce.